Neurovascular coupling in patients with type 2 diabetes mellitus - Canna, Antonietta; Esposito, Fabrizio; Tedeschi, Gioacchino; Trojsi, Francesca; Passaniti, Carla; di Meo, Irene; Polito, Rita; Maiorino, Maria Ida; Paolisso, Giuseppe; Cirillo, Mario; Rizzo, Maria Rosaria (Frontiers in Aging Neuroscience, 2022)
Functional and metabolic neural changes in Type 2 diabetes mellitus (T2DM) can be associated with poor cognitive performances. Here we analyzed the functional-metabolic neurovascular coupling (NVC) in the brain of T2DM patients. Thirty-three patients (70±6 y, 15 m) with recent T2DM diagnosis and 18 healthy control (HC) subjects (65±9 y, 9 m) were enrolled in a brain MRI study to identify the potential effects of T2DM on NVC. T2DM patients were either drug-naive (n=19) or under treatment with metformin (n=14) since less than 6 months. Arterial spin labeling and blood oxygen level dependent resting-state functional MRI (RS-fMRI) images were combined to derive NVC measures in brain regions and large-scale networks in a standard brain parcellation. Altered NVC values in T2DM patients were correlated with cognitive performances spanning several neurological domains using Spearman correlation coefficients. Compared to HC, T2DM patients had reduced NVC in the default mode network (DMN) and increased NVC in three regions of the dorsal (DAN) and salience-ventral (SVAN) attention networks. NVC abnormalities in DAN and SVAN were associated with reduced visuo-spatial cognitive performances. A spatial pattern of NVC reduction in the DMN, accompanied by isolated regional NVC increases in DAN and SVAN, could reflect the emergence of (defective) compensatory processes in T2DM patients in response to altered neurovascular conditions. Overall, this pattern is reminiscent of neural abnormalities previously observed in Alzheimer’s disease, suggesting that similar neurobiological mechanisms, secondary to insulin resistance and manifesting as NVC alterations, might be developing in T2DM pathology.